Pengaruh Faktor-Faktor Atraksi Amenitas Dan Aksesbilitas Terhadap Strategi Pengembangan Wisata Halal Bromo - Dian Cahyo Prabowo; Ernani Hadiyati; Sugeng Mulyono; Ahmad Ahmad (Jurnal Sains Sosio Humaniora, 2021)
Nowadays, the concept of Islamic economics is an important part of global economic life. In the concept of Islamic economics, there is a concept of halal. The concept of halal in Islamic economics has been developed into various products including banking, hotels/lodging, insurance and tourism in term of syariah. Halal tourism is one of the new phenomena in the tourism sector. One of the tourist areas that developed this halal concept is Mount Bromo tourism. The development of the concept of halal tourism on Mount Bromo is very interesting to study in relation to the different characteristics between the majority of the population around Mount Bromo who are Hindus and the target tourists who are Moslem. This study aims to examine and analyze the influence of attractions, amenities, and accessibility on the development strategy of Mount Bromo halal tourism. Attraction means anything that has uniqueness, beauty, and value in the form of a diversity of natural, cultural, and man-made wealth that is the target or purpose of a tourist visit. Amenities are various facilities that must be provided by a tourist destination. Accessibility is the ability to reach a certain tourist destination. This explanatory research was conducted in the tourist area of ​​Mount Bromo in 2019. The type of data in this study is qualitative which were processed into quantitative data. Data were collected through a questionnaire distribution method. The variables in this study were measured using a Likert scale. Furthermore, the data were analyzed by using the SPSS 18 program (Statistical Product and Service Solution). The results of this study are: 1) Attraction variables have a positive and significant effect on the Development Strategy for halal tourism in Mount Bromo; 2) The amenities variable directly has a positive and significant effect on the Development Strategy for halal tourism in Mount Bromo; 3) The accessibility variable has a negative and insignificant effect directly on the Development Strategy for halal tourism in Mount Bromo; 4) The variables of attractions, amenities and accessibility together have a positive and significant effect on the development strategy of halal tourism in Mount Bromo.